Article history: Received March 10, 2024 Revised Oct 14, 2024 Accepted Nov 20, 2024 Keywords: Influence, Flashcard Media, Vocabulary Mastery Pengaruh Media Flashcard Terhadap Penguasaan Kosakata Bahasa Inggris - Krisdiyanti, Dini; Susilo, Claudya Zahrani (Prodi Pendidikan Guru Sekolah Dasar, 2024)
There are many problems that occur in English education, one of which is that learning is still centered on teachers and textbooks. Students are accustomed to learning using the lecture method. Learning like this and without media can create a less active classroom atmosphere, as indicated by a less conducive classroom atmosphere, some students are busy chatting when the teacher explains in front of the class. The purpose of this research is to find out how flashcard media influences vocabulary mastery in the English subject Where Is My Pencil for class IV at SD Negeri Rejoagung 3. This research is a quantitative research with the type of Pre-Experimental Design research in the form of OneGroup Pre-test-Post -test. The population was all fourth grade students at SD Negeri Rejoagung 3. The sample taken in this research consisted of one class totaling 18 students. The method used in this research is test questions. The test is a written test in the form of multiple choices. The results of this research produced conclusions namely: (1) the ability to understand material about Where Is My Pencil in class IV students at SD Negeri Rejoagung 3 before using flashcard media was generally categorized as moderate with the average score obtained being 46.67. (2) Meanwhile, after using flashcard media, it was generally categorized as capable with the average score obtained being 66.11. (3) the influence of learning English with Where Is My Pencil material on fourth grade students at SD Negeri Rejoagung 3 shows that there is a significant influence of 0.000. The significant value shows 0.000 < 0.05 so that H₀ is rejected and Ha is accepted, which means that there is a significant influence in the use of flashcard media on the English vocabulary mastery of class IV students at SD Negeri Rejoagung 3.